2023
DOI: 10.1021/acs.jafc.2c08519
|View full text |Cite
|
Sign up to set email alerts
|

Swainsonine Induces Liver Inflammation in Mice via Disturbance of Gut Microbiota and Bile Acid Metabolism

Abstract: Swainsonine induced liver inflammation in livestock; however, the underlying mechanisms, especially the role of bile acids (BAs), in the pathogenesis remained elusive. Here, our results showed that swainsonine induced hepatic inflammation via changing BA metabolism and gut microbiota in mice. Swainsonine significantly upregulated the levels of deoxycholic acid (DCA) and taurine-β-muricholic acid (T-β-MCA) in the serum and liver of mice due to the markedly increased genus Clostridium and the decreased genus Lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…According to our previous findings, swainsonine induced hepatic inflammation by modulating intestinal microbes and their bile acid metabolites . In the present study, swainsonine treatment regulated the gut microbial composition as well as the levels of microbially derived indole metabolites.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…According to our previous findings, swainsonine induced hepatic inflammation by modulating intestinal microbes and their bile acid metabolites . In the present study, swainsonine treatment regulated the gut microbial composition as well as the levels of microbially derived indole metabolites.…”
Section: Discussionsupporting
confidence: 74%
“…Targeted 500 metabolomics were used to obtain a comprehensive profile of liver and serum metabolites in different groups. The results of liver pathology and biochemical indexes that swainsonine induced hepatic inflammation in mice have been described in the previous study . We visualized the differences in the metabolites of the liver and serum using the OPLS-DA model score plots (Figure ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous results genomic study showed consistent enrichment in bile metabolism and drug metabolism-cytochrome P450 when rat renal tubular epithelial cells were exposed to the same conditions as in this study. Additionally, Fu et al ( 25 ) demonstrated that SW induced liver inflammation by altering bile acid metabolism and intestinal microbiota in mice. Thus, these results suggest that exposure to SW may significantly alter the bile acid metabolism whether these changes is associated with the SW-induced cellular damage remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, research papers exploring the intoxication mechanisms of SW are highly limited, with only a solitary study identified. In this study, the author cleverly harnessed targeted metabolomics and high-throughput sequencing techniques to reveal that SW has the capacity to profoundly alter bile acid metabolism and disrupt the delicate balance of intestinal microbiota in mice, ultimately triggering inflammatory reactions in the liver ( 25 ). Nevertheless, our understanding of the kidney toxicity and associated metabolites triggered by SW remains tenuous, necessitating further investigation in this vital area.…”
Section: Introductionmentioning
confidence: 99%